Carers of patients with high-grade glioma report high levels of distress, unmet needs, and psychological morbidity during patient chemo radiotherapy - Long, A.; Halkett, Georgia; Lobb, E.; Shaw, T.; Hovey, E.; Nowak, A. (2015)
Background: Few studies have explored the unmet needs of carers of people with high-grade glioma. We aimed to determine carers' levels of distress during treatment, understand their support needs and explore predictors of distress. Methods: Carers of people with high-grade glioma undergoing chemoradiotherapy were recruited to this prospective, longitudinal cohort study. Carers completed the validated Supportive Care Needs Survey, Brain Tumour Specific Supportive Care Needs Scale, Distress Thermometer (DT), and General Health Questionnaire (GHQ-12). Questionnaires were administered during patients' chemoradiotherapy and 3 and 6 months later. Results: We recruited 118 carers who were mainly female (72%) and caring for spouse (82%). The mean age was 53 years (SD = 13.6; range, 21-89). Thirty-one percent of carers reported moderate distress (DT score 5-6/10) and 31% reported extreme distress (score 7-10/10) during combined chemoradiotherapy. Carer distress was associated with adverse GHQ scores (r = 0.61, P < .001). Seventy-two percent reported a negative financial impact of caring and 51% of those previously working full-time had taken leave or reduced working hours. The top 5 moderate/high unmet needs were: accessing prognostic information; accessing financial support and government benefits; accessible hospital parking; impact of caring on usual life; reducing stress in the patients' life. Conclusion: Carers reported substantial distress, and high distress levels were correlated with greater psychological impact and increased self-reporting of unmet needs. Future research should focus on interventions that aid in reducing carer distress.